The greatest lie of all [large type] - Cantor, Jillian (Thorndike Press large print dynamic drama., 2024)
"Fledgling actress Amelia Grant is at rock bottom when offrered the opportunity to star in a biopic about the world-renowned romance author Gloria Diamond, who used her own tragic love story as inspiration for her bestselling books. To prepare for the role, she'll spend a week with Gloria at her secluded Washington estate. Amelia's excitement is short-lived, however, once she actually meets Gloria, who is cold, verging on rude. When Amelia stumbles upon a secret from Gloria's past, she realizes Gloria's life story is more fiction than fact. And as the movie's filming date draws nearer, Amelia must decide how much she's willing to sacrifice to uncover the truth."--from back cover.